In the heat of the moment: Bringing 'Je suis Charlie' into focus. (August 2016) - Klug, Brian
In the immediate aftermath of the murderous attack on the offices of Charlie Hebdo, millions of people rallied round the slogan 'Je suis Charlie'. The slogan conveyed a simple message: either you are in favour of free speech and the right to offend or you are against. This essay offers a critique of the slogan and its message. The first part raises and discusses the problem of framing: what, fundamentally, was the Paris attack about? The middle section discusses a blog that I posted at the time, also written in the heat of the moment. This segues into the third and final part, which examines the language of rights, freedom of expression and the meaning of the word 'offend'. The conclusion drawn is that the slogan 'Je suis Charlie' is an obstacle to thinking through the issues raised by the Paris attack.